Congenital Cytomegalovirus Knowledge, Practices, and Beliefs Among Primary Care Physicians and Newborn Hospitalists - Megan H. Pesch; Kathleen M. Muldoon (SAGE Publishing, 2022)
Background: Congenital cytomegalovirus (cCMV) affects 1 in every 200 United States infants, at present there are 9 states which mandate newborn cCMV screening. With more infants being diagnosed, more children will need continuing care from providers who are knowledgeable about cCMV. Objectives: To examine pediatric provider knowledge, practices, and beliefs around cCMV. Methods: Primary care and newborn hospitalist pediatricians (N = 103) from Michigan, who "regularly care for infants" were invited to participate in a survey about their cCMV-related knowledge, clinical practices, and beliefs. Results: Respondents had low knowledge of typical cCMV presentation and sequelae, with mixed knowledge of screening and testing standards. Most (68%) reported rarely/never screening for cCMV, though 71% strongly agreed/agreed that primary care providers should test for cCMV. Most (90%) strongly agreed/agreed that infants who fail/refer on their newborn hearing screen should be tested for cCMV, yet 81% expressed not being comfortable diagnosing and managing cCMV. Most (72%) felt that cCMV was not sufficiently covered in their medical training; almost all respondents endorsed interest in learning more. Conclusions: Primary care and newborn hospitalists in this study expressed mixed knowledge about, infrequent practice of and low comfort with screening and caring for children with cCMV. This may present a prime opportunity for education and clinician support by professional organizations.